La crisi delle relazioni amorose nell’opera di Giovanni Agnoloni - Kopańska, Karolina (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
In this article, the author attempts to examine love relationships in the world onthe brink of catastrophe, described in the works of Giovanni Agnoloni. The Florentine writerpresents a vision of the world after the collapse of the Internet, a world in an economic,technological and social crisis. The author will try to prove the thesis that with the fall ofcivilization, love relationships are also troubled.